Pengembangan Sistem Informasi Manajemen Klinik berbasis Web (Studi Kasus: Klinik Ortho Dental Malang) - Muhammad Yusuf Saputra; Adam Hendra Brata; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Ortho Dental Clinic is a health service facility that provides dental and oral health services located on Jalan Raya Tlogomas, Malang, East Java. The services provided by the Malang Ortho Dental Clinic include installing stirrups, veneers, scaling and installation of dentures. Problems at the Malang Ortho Dental Clinic are difficulties in ordering and registering patients, there is no medical record system, missing transaction data and inaccurate transaction reports. From these problems, a web-based Ortho Dental Malang SIMK was developed which can facilitate the process of ordering care and patient registration, recording of medical records, transactions and transaction reports. The development of SIMK Ortho Dental Malang uses the waterfall model and produces 5 actors namely user, admin, doctor, front office, patient, 1 non-functional requirement and 48 functional requirements. The results of the validation test and SIMK Ortho Dental Malang unit are 100% valid. The results of SIMK Ortho Dental Malang compatibility testing using the SortSite tool show that the system is compatible with desktop web browsers Edge, Firefox, Opera, Safari, Chrome and web browsers on Android and iOS.